1997
DOI: 10.1111/j.1467-8624.1997.tb01953.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Agent and Social Context in Judgments of Freedom of Speech and Religion

Abstract: This study examined children's, adolescents', and college students' judgments of the rights of child and adult agents to freedom of speech and religion in 3 social contexts: the general level of society, the school, and the family. Two hundred forty participants, evenly divided into 5 grade levels (mean ages 6,6, 8,5,10,6,12,4, and 22,7) made judgments of the legitimacy of authority prohibition, rule evaluation, generalizability, and rule violation for all freedom/social context/agent combinations. Concepts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
69
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 35 publications
10
69
2
1
Order By: Relevance
“…Older children appeared to have a greater appreciation of the importance of religious freedom and parental autonomy and were critical of government intrusion into the religious and family sphere in this instance. These findings parallel those from studies of children's developing conceptions of freedom of religion (Helwig, 1997) showing that with age, the religious freedom of children is increasingly seen as legitimately regulated by familial authorities (e.g., parents), but not by governments or school authorities. Prior research (Helwig, 1997), however, investigated conceptions of religious freedom only in straightforward or "prototypical" examples, in which freedom of religion did not conflict with other social goals.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Older children appeared to have a greater appreciation of the importance of religious freedom and parental autonomy and were critical of government intrusion into the religious and family sphere in this instance. These findings parallel those from studies of children's developing conceptions of freedom of religion (Helwig, 1997) showing that with age, the religious freedom of children is increasingly seen as legitimately regulated by familial authorities (e.g., parents), but not by governments or school authorities. Prior research (Helwig, 1997), however, investigated conceptions of religious freedom only in straightforward or "prototypical" examples, in which freedom of religion did not conflict with other social goals.…”
Section: Discussionsupporting
confidence: 78%
“…The present study sought to examine legal judgments by comparing and contrasting laws that have socially beneficial purposes with unjust laws, and by examining reasoning in situations that entail conflicts between social benefits and individual rights and autonomy. This strategy is similar to one pursued in other research on children's judgments of societal, political, and moral concepts such as civil liberties and democracy, and has proven successful in uncovering new competencies in elementary school children's understanding in these areas (Helwig, 1997(Helwig, , 1998Helwig & Kim, 1999). The results of the present study reveal that children's reasoning about laws is multifaceted and that children consider a number of factors in evaluating laws and making judgments of legal compliance.…”
Section: Discussionmentioning
confidence: 59%
“…However, research examining children ' s reasoning about rights and democracy shows that these concepts have emerged by the early elementary school years. For example, research investigating children ' s and adolescents ' reasoning about freedom of speech and religion (Helwig, 1995(Helwig, , 1997(Helwig, , 1998 found that by 6 years of age, children judge restrictions of these rights by governments or other authorities as wrong and illegitimate. Moreover, children, adolescents, and adults view freedom of speech and religion as moral rights that should be upheld in all countries.…”
Section: The Development Of Concepts Of Autonomy Rights and Democracymentioning
confidence: 99%
“…Using this approach, researchers have found that by around 10 years of age, most children view participation and decision making as important children's rights (Ruck, Keating, Abramovitch, & Koegl, 1998). In addition, Helwig (1995Helwig ( , 1997 reported that, in contrast to the earlier work of Melton (1980), abstract concepts of freedom of speech and religion were found in some children as young as six years of age.…”
Section: Children As Citizensmentioning
confidence: 83%